2006
DOI: 10.1007/s10545-006-0411-z
|View full text |Cite
|
Sign up to set email alerts
|

Glucosylceramide transfer from lysosomes—the missing link in molecular pathology of glucosylceramidase deficiency: A hypothesis based on existing data

Abstract: SummaryGaucher disease (GD), deficiency of acid glucosylceramidase (GlcCer‐ase) is characterized by deficient degradation of beta‐glucosylceramide (GlcCer). It is well known that, in GD, the lysosomal accumulation of uncleaved GlcCer is limited to macrophages, which are gradually converted to storage cells with well known cytology—Gaucher cells (GCs). On the basis of previous studies of the disorder and of a comparison with other lysosomal enzymopathies affecting degradation of the GlcCer‐based glycosphingolip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 107 publications
(106 reference statements)
2
33
0
1
Order By: Relevance
“…However, poorly responsive variants of GD1, such as cancers, Parkinson disease, hepatocellular disease, and osteoporosis, have emerged. This clinical complexity seen with a single gene defect, in essence, underscores our limited understanding of the multiple cell types and pathways that are likely involved in the pathogenesis of GD1 (17). Here, we report that a mouse in which the GBA1 gene was deleted conditionally using an Mx1 promoter recapitulated the human disease almost in its entirety.…”
Section: Discussionmentioning
confidence: 92%
“…However, poorly responsive variants of GD1, such as cancers, Parkinson disease, hepatocellular disease, and osteoporosis, have emerged. This clinical complexity seen with a single gene defect, in essence, underscores our limited understanding of the multiple cell types and pathways that are likely involved in the pathogenesis of GD1 (17). Here, we report that a mouse in which the GBA1 gene was deleted conditionally using an Mx1 promoter recapitulated the human disease almost in its entirety.…”
Section: Discussionmentioning
confidence: 92%
“…Our findings will permit a more thorough assessment of the potential role of GBA2 in Gaucher disease, especially because, in Gaucher cells, the accumulation of GlcCer appears not to be limited to the endolysosomal compartment (93). Aureli et al (85) and Burke et al (86) recently reported that the GBA2 activity is increased in Gaucher fibroblasts and leukocytes and in GBA-deficient mouse brains, and Körschen et al (11) found that the GBA2 activity is reduced in murine GBA-deficient fibroblasts and in type 2 Gaucher fibroblasts.…”
Section: Nb-dnj Nb-dgj Amp-dnj ؊Cbementioning
confidence: 96%
“…Increasing clinical evidence suggests that the pathophysiology of classic GD is more complex and involves system-wide dysfunction of cell types other than macrophages (3)(4)(5). The involvement of immune cells has been implicated, but the underlying molecular defect is poorly understood (6)(7)(8)(9).…”
mentioning
confidence: 99%